ROV’s Video Recordings as a Tool to Estimate Variation in Megabenthic Epifauna Diversity and Community Composition in the Guaymas Basin - López-Garrido, Pedro H.; Barry, James P.; González-Gordillo, Juan Ignacio; Escobar-Briones, Elva (Frontiers in Marine Science, 2020)
Patterns in benthic megafauna diversity in littoral and intertidal zones in the Gulf of California has been associated as a function of habitat heterogeneity and substrate type. Current knowledge of invertebrate communities in hard bottom habitats at depths >200 m in the Gulf is poor due to the methodological limitations inherent in sampling deep habitats. Using benthic imagery recorded on video coupled with environmental data from the Remotely Operated Vehicle Doc Ricketts, we documented variation in the diversity and community composition of the benthos from 849-990 m depth in the NW limit of the Guaymas Basin in relation to dissolved oxygen and substrate characteristics. This area is affected by the incidence of an oxygen minimum zone where oxygen drops to levels <0.5ml L-1 and strong gradients in a narrow depth range occur. Dissolved oxygen varied along our benthic survey from 0.200 to 0.135 ml L-1. We observed a great taxonomic richness across an area of rocky outcrops through the lower transitional zone. This megafaunal pattern is different to that reported in other oxygen minimum zones where they are characterized by a great abundance of a few species. Taxonomic richness diminished at depths with reduced dissolved oxygen in the lower boundary of the oxygen minimum zone with increasing soft sediment cover. We found that rocky outcrops (including structure-forming organisms such as corals, sponges and oyster aggregations also provide a hard substrate for other fauna) supported a higher diversity (H’= 0.8) than soft sediment (H´=0.7) as have been observed in other habitats such as seamounts. Environmental variables that explained most of the megafaunal variation were substrate type (18.4%), depth (1.14%) and temperature (0.9%). Salinity (0.45%) and dissolved oxygen (0.3%) were less important factors to explain the megafaunal composition variance. Substrate type played a key role in the diversity and composition of benthic megafauna. These results broaden our understanding concerning the potential roles of substrate characteristics in the community composition of the deep-sea benthic megafaunal assemblages in the Gulf of California and oxygen minimum zones in general.